Short-term heavy drinking in a non-human primate model skews monocytes toward a hypo-inflammatory phenotype - Blanton, Madison B.; Hemati, Hami; Qiao, Qi; Khadka, Rupak; Hawk, Gregory; Grant, Kathleen A.; Messaoudi, Ilhem (Frontiers in Immunology, 2025)
IntroductionAlcohol use is prevalent in the United States (US), with ~80% of persons over 12 years old reporting alcohol consumption in 2023 and ~10% of those individuals developing alcohol use disorder (AUD). Acute and chronic alcohol consumption exert opposite effects on the immune system. Specifically, acute alcohol exposure (AAE), (3–16 hours of in-vitro treatment, one binge episode in humans, or one gavage feeding in mice) skews monocytes towards a hypo-inflammatory phenotype associated with reduced TNFα, IL-6, and MCP-1 production. In contrast, chronic alcohol consumption (CAC) (7 days of in-vitro treatment, 3–12 months of consumption in animal models, or humans with confirmed AUD diagnosis), shifts the functional, transcriptional, metabolic, and epigenetic landscapes of monocytes and their progenitors towards a hyper-inflammatory profile. Despite the extensive work investigating AAE and CAC, few studies have examined short-term drinking durations. We sought to bridge this gap by assessing monocytes after 6 months of ethanol consumption in a rhesus macaque model, which we considered short-term drinking. Understanding the longitudinal changes in monocytes’ phenotype and function in the context of alcohol consumption could pave the way to identifying diagnostic biomarkers for disease progression.MethodsTo bridge this gap, we obtained peripheral blood mononucleated cells (PBMC) isolated from rhesus macaques before and after 6 months of daily ethanol consumption (>55% of intakes over 2.0 g/kg/day). Monocytes were analyzed using a combination of flow cytometry, single-cell RNA-sequencing (scRNAseq), ELISAs, and Cleavage Under Targets and Tagmentation (CUT&Tag).ResultsOur data show that 6 months of ethanol consumption rewires monocytes towards a hypo-inflammatory profile as evidenced by reduced cytokine production. scRNAseq analysis revealed distinct shifts in monocyte states/clusters with ethanol consumption and LPS stimulation in line with a shift to a hypo-inflammatory state. These changes may be driven by reduced levels of H3k4me3, a histone modification shown to be deposited at promoter regions of genes involved in inflammation and pathogen response signaling.DiscussionOverall, these data demonstrate that 6 months of daily heavy drinking attenuates inflammatory responses in monocytes via shifts in the epigenetic landscape.